Water pollution effects of river Saraswati and Kunti on livelihood: a case study of fishermen communities in Tribeni and Kuntighat, Hooghly, West Bengal - A. K. Panigrahi; Subasini Pattnaik (Journal of Fisheries, 2020)
A prolific study was conducted to find out the impact of pollution on the socio-economic status of the fishermen community of Tribeni, Kuntighat - Hooghly, West Bengal, who depend on the rivers Saraswati, Kunti and Ganga for their livelihood. Analysis of important water quality parameters clearly reflects the pollution status of the rivers Saraswati and Kunti. Investigation was carried out by a previously tested questionnaire and personal interaction with 100 fishermen based on which the probable reasons of decline in fish diversity were drawn, which consequently adversely affected the economic conditions of fishermen. The investigation revealed a positive correlation between discharge of industrial effluents, in turn depleting the availability of fish food organisms and fish diversity and warning socioeconomic conditions of fishermen. Results clearly indicate proper steps should be taken by the policy makers towards restoration of water quality and thereby helping the vulnerable fishermen.